Maxim Violation as A Defense Mechanism in A Fictional Character: A Pragmatic–Psychoanalytic Analysis of Wednesday - Azzahra , Xelga; Prihandini, Asih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study investigates how violations of Gricean conversational maxims function as manifestations of Freudian defense mechanisms in fictional discourse. The data are drawn from a therapy session in Episode 1 of the Netflix series Wednesday (2022), focusing specifically on Wednesday Addams’ responses to questions concerning the rejection of her literary work. Employing a qualitative interpretive approach, the analysis integrates Grice’s Cooperative Principle with Freud’s theory of ego defense mechanisms. The data collection process proceeded in several stages. In the first stage, the selected episode was watched thoroughly and was repeatedly view. In the second stage, all the dialogue in the selected episode was transcribed. In the third stage, the transcribed utterances were reviewed and organized into a structure data set. The findings reveal that Wednesday violates the Maxim of Manner by avoiding direct responses and the Maxim of Quality through evaluative overgeneralization. These violations function as rationalization strategies that protect her ego from psychological threat posed by repeated rejection. Rather than representing communicative failure, the maxim violations operate as strategic linguistic choices that preserve self-image and deflect vulnerability. This study demonstrates that integrating pragmatic theory with psychoanalytic interpretation enables a deeper understanding of the psychological motivations embedded in fictional dialogue. The findings contribute to interdisciplinary scholarship by illustrating how conversational structure can reveal latent emotional architecture in character construction